(3Gdeaghe GdMOjK dEOGQI GdJShjb (B/s - (3Lj, CHj SYjO GdOjhgs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ(B, s, 2000)
(3GdeONd dOQGSI GdJShjb, eaghe GdeRjL GdJShjbj hYfGUQg, Sdhc GdeSJgdc hbQGQGJ GdTQGA, JbSje GdShb hGdJfHD HGdeHjYGJ, HMhK GdJShjb hfXe GdeYdheGJ GdJShjbjI, GdefJL, GdJYHFI hGdJZdja, GdJhRjY hGdbfhGJ GdJhRjYjI, JLGQI GdLedI, JLGQ GdeaQO, GdJhRjY GdeGOj, GdJQhjL, GdEYdGf, JfTjW GdeHjYGJ, GdHjY GdTNUj, GdJSYjQ, JShjb GdNOeGJ, GdJShjb GdOhdj, GSJQGJjLjI GdJShjb hGdQbGHI YdjgG, GdJShjb aj GdefXeGJ Zj GdQHMjI, GdEYJHGQGJ GdCNdGbjI hGdELJeGYjI ddJShjb, GdJShjb GdeHGTQs
(3HHdjhZQGajG U(B.499(3; cTGa eUWdMGJ U(B.490s
Keywords: (3GOGQI GdeHjYGJs; (3GdJShjbs